The bee genus Ruizantheda (Hymenoptera: Halictidae), its scope and description of a new species - Gonzalez-Vaquero, Rocio Ana; Roig-Alsina, Arturo (Zootaxa, 2009)
The South American caenohalictine genus Ruizantheda is understood to comprise Halictus proximus Spinola, Halictus divaricatus Vachal, and the new species Ruizantheda centralis from Argentina. The new species is intermediate between the first two, bridging the gap in morphology observed in these rather different species. Diagnostic characteristics for the genus are indicated; a key and a comparative table of characters for the three species are given. The new species, which occurs in the provinces of Santa Fe, Santiago del Estero and Chaco, in Argentina, is described and illustrated.